Seizing Opportunity from Crisis : Making Multilateralism Work - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, recalled a moment in John Maynard Keynes life when he called for deeds that restore the public trust that governments are up to the challenge of the current crisis. What started in 2007 as a financial crisis quickly spiraled into an economic crisis, with estimates for 2009 for the first contraction of the global economy since World War II and the largest decline of trade in 80 years. Developing countries are being battered in successive waves as private capital flows slump sharply. These events could next become a social and human crisis, with political implications. Zoellick reviewed the difficulties for each region of the world. Unlike the 1930s, however, central banks have stepped in with creative solutions to keep credit flowing. But the challenge ahead requires a spirit of innovation backed by action. The World Bank Group’s Board is considering a new proposal: the launch of a $50 billion Global Trade Liquidity Program. Zoellick called for the member of the G-20 to make multilateralism work and to empower the WTO, the IMF, and the World Bank Group to monitor national policies. Bringing sunlight to national decision-making would contribute to transparency, accountability, and consistency across national policies. It is time to institutionalize “early warning” systems to protect the poor from cuts in social programs during times of economic crisis. Modern multilateralism will require that rising economic powers have a larger say in how institutions such as the World Bank and the IMF are run.